PERANAN HUKUM ISLAM BAGI UMMAT MUSLIM DI INDONESIA (“THE ROLE OF ISLAMIC LAW FOR MOSLEM FOLLOWERS IN INDONESIA”) - MUDEMAR A. RASYIDI (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTIslamic Law is rooted at wahyu illahi. That is Al’Quran, and prophets words, Al-Hadist, aswell as the teaching of Ulama on consensus of a great number of religious scholars or peoplewho had knowledge about Islam that agreed upon to decide a determination or the regulationof law groove dealing with the case of life on the world.Islamic law is not only bused on the nature of religion but also Qiyas that was taken fromAl’Quran and Al-Hadist, as a guidence or example in determinating a decision, and also ijtihad.All those were Used as a guide in corriying out life on this the mortal world nature in orderto All moslem followers within doing life on this world. They could do the honest law full, couldbe trusted and right. Expectantly, to obtain blessing of Allah SWT, As a final point, to achieve ahappines on the world of the hereafter.Keywords : Religion, Islamic Law, Al-Qur’an, Al-Hadist, Shari'a religious